2021
DOI: 10.37871/jbres1218
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Drug-Resistant Mycobacterium tuberculosis in Sputum Specimens from the New and Previously Treated Tuberculosis Cases at the National Reference Chest Diseases Laboratory in Lusaka, Zambia

Abstract: Background: Drug-Resistant Tuberculosis (DR-TB) is one of the major public health issues globally. Zambia is highly burdened by TB and multi-drug resistant TB. In this study, sputum samples obtained from the new and previously treated cases of TB were examined for drug-resistant Mycobacterium tuberculosis (MTB). Methods: Sputum specimens were processed using the N-acetyl-L-cysteine-sodium hydroxide method, stained and examined using fluorescent technique and microscopy respectively. Mycobacterial DNA was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 83 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…Isoniazid resistance is brought about by mutations in several genes of M. tuberculosis such as the katG, inhA, ahpC, kasA, oxyR, furA, fabG1-inhA, and ndh genes. 3,34,37 However, Current research has shown that resistance to isoniazid can also be caused by an upregulation of efflux pumps or isoniazid inactivators. 38,39 Mutations in the katG, inhA and its promoter, and the oxyR-ahpC intergenic region frequently confer resistance to INH.…”
Section: Drug Target Genes and Mutations Conferring Resistance To Iso...mentioning
confidence: 99%
See 4 more Smart Citations
“…Isoniazid resistance is brought about by mutations in several genes of M. tuberculosis such as the katG, inhA, ahpC, kasA, oxyR, furA, fabG1-inhA, and ndh genes. 3,34,37 However, Current research has shown that resistance to isoniazid can also be caused by an upregulation of efflux pumps or isoniazid inactivators. 38,39 Mutations in the katG, inhA and its promoter, and the oxyR-ahpC intergenic region frequently confer resistance to INH.…”
Section: Drug Target Genes and Mutations Conferring Resistance To Iso...mentioning
confidence: 99%
“…1,2 It causes high mortality and morbidity rates, it kills one person every 21 seconds. 3,4 TB is caused by species of the Mycobacterium tuberculosis complex (MTBC), some of which are adapted to humans (Mycobacterium tuberculosis [MTB] and Mycobacterium africanum), while others to animals (Mycobacterium bovis, Mycobacterium microti, Mycobacterium pinnipedii, Mycobacterium mungi, and Mycobacterium caprae), and others are smooth bacilli (Mycobacterium canettii). [5][6][7] MTB is the major causative pathogen for human TB among the species of MTBC, as it causes 97-99% of all TB cases globally.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations